(untitled) (Journal of Training and Development, 2016)
HIV and AIDS are crucial issues throughout the world. The first case in Nepal was diagnosed in 1988. Due to poverty, most of the people from the rural region of Nepal i.e. from the mid and far western region migrates to the neighboring country India to find work. During their stay in India, due to unsafe sex these migrants gets infected with HIV and AIDS. After returning home these migrants transmits the diseases to their spouses. The children born from infected parents also gets infected as well. The lack of technical education and vocational training compel these people to migrate in India to search for job without having any basic skill. The lack of knowledge on sexually transmitted diseases also increases the probability of getting infected. Therefore, it is necessary to make the people from the rural parts of Nepal aware of the sexually transmitted diseases, its causes and precautions. In addition, providing technical education and vocational training to rural people will enable them to secure more reliable job both outside and within the country.